Peran Coretax dalam Kepatuhan Wajib Pajak Pelaporan PPH 21 di Indonesia - Jeconiah Nathanael; Condro Widodo (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The Directorate General of Taxes is tactically aiming to improve effectiveness and compliance in tax collection, utilizing Coretax as its tool to digitalize its tax administration. The same applies to income tax Article 21 (PPh 21) reporting. This study aims to examine the extent to which the application of the Coretax system has brought about a change in the way Indonesian taxpayers comply with the regulations and pay their taxes. This paper uses a descriptive qualitative approach based on literature to explain how putting services, for example, e-SPT, e-Bupot, and e-Billing, into Coretax simplifies the filing process, reduces inaccuracy, and enhances transparency and the level of control of the government through hierarchy. The analysis reveals that Coretax has done what it intended: make reporting more useful and build taxpayer trust. However, there are still challenges to implementing the plan, especially around uneven technological infrastructure and digital literacy. So, interagency cooperation, training, and improving the user interface are all-important recommendations for ensuring that Coretax is used fairly across the country.